2016
DOI: 10.1111/eea.12475
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavioral response of cotton aphid, Aphis gossypii, to elevated CO2: EPG test with leaf microstructure and leaf chemistry

Abstract: Effect of elevated CO 2 on feeding behavior of the cotton aphid, Aphis gossypii (Glover) (Hemiptera: Aphididae), was investigated using electrical penetration graphs (EPG) on cotton, Gossypium hirsutum L. (Malvaceae). Leaf microstructures and foliar soluble constituents were also measured simultaneously to quantify the impact of foliar changes on leaf nutritional quantity and quality, owing to elevated CO 2 , on stylet penetration and food-quality plasticity of A. gossypii. Significant increases in fresh body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 61 publications
6
26
0
Order By: Relevance
“…A study on Gastrophysa viridula (DeGeer) showed that female fecundity of the second generation reduced by 30% compared to that of the first generation in elevated CO 2 (600 ppm) (Brooks & Whittaker, 1998). Thus, elevated CO 2 may only have significant effects after a number of generations (Awmack et al, 1997;Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A study on Gastrophysa viridula (DeGeer) showed that female fecundity of the second generation reduced by 30% compared to that of the first generation in elevated CO 2 (600 ppm) (Brooks & Whittaker, 1998). Thus, elevated CO 2 may only have significant effects after a number of generations (Awmack et al, 1997;Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this study lacks in a factorial design (i.e., two aphid treatments*two plant treatments) and cannot inform whether an increase in CO 2 concentration affects aphids, plants, or both. Thus, based on evidence of aphid feeding behavior being modified (Guo et al, 2013(Guo et al, , 2014Jiang et al, 2016; Tre z bicki (Ode et al, 2014), we hypothesize that the observed increase in transmission efficiency may be attributed to one of these factors. With this in mind, we can speculate that the feeding behavior of aphids is dependent on plant defenses, and would modify their potential transmission efficiency.…”
Section: Discussionmentioning
confidence: 95%
“…Thus the growth and development of herbivorous and sap-sucking insects is indirectly altered by elevated CO 2 through its direct effects on plant biomass and nutrient compositions (Kazan, 2018;Li et al, 2019a). In general, elevated CO 2 triggers population growth of sap-sucking insects such as aphids (e.g., Myzus persicae), whiteflies (e.g., Bemisia tabaci), and planthoppers (e.g., Nilaparvata lugens) (Jiang et al, 2016;Li et al, 2019a). However, the growth, survival rates and population density of most leaf-chewing insects are suppressed by elevated CO 2 possibly because of the potential deterioration of nutrient quality of their feeds (Coll and Hughes, 2008;Kazan, 2018).…”
Section: Defense Response Of Tea Plants As Influenced By Elevated Comentioning
confidence: 99%